Asynchronous instability of the North American-Arctic and Greenland ice sheets during the last deglaciation. (15th May 2017) - Jackson, Rebecca; Carlson, Anders E.; Hillaire-Marcel, Claude; Wacker, Lukas; Vogt, Christoph; Kucera, Michal
Abstract: The chronology of deglacial meltwater pulses from the Laurentide Ice Sheet is well documented. However, the deglacial history of the North American-Arctic (north-eastern Laurentide and Innuitian) and western Greenland ice sheets draining into the Labrador Sea via Baffin Bay is less well constrained. Here we present new high-resolution, radiocarbon-dated records from the central Baffin Bay spanning ∼17 to 10 kyr BP and documenting the full deglacial history of Baffin Bay. Sedimentological and geochemical data confirm the presence of two periods of enhanced detrital carbonate delivery, termed Baffin Bay Detrital Carbonate Events (BBDCs). These events are dated to ∼14.2–13.7 kyr BP and ∼12.7–11 kyr BP. They are synchronous across Baffin Bay and their mineralogical signature indicates a common source of detrital carbonate from northern Baffin Bay. The first event, BBDC 1, postdates Heinrich Event 1 and the second event, BBDC 0, predates the recently revised timing of Heinrich Event 0. The onset of the BBDC events appears not to be systematically linked to Greenland temperature change as they occur during both interstadial and stadial periods. This indicates that deglaciation of North American-Arctic and western Greenland ice sheets with the associated iceberg and meltwater discharge were decoupled from the dominant North Atlantic climate mode, where iceberg discharge events from the Laurentide Ice Sheet occurred during stadial periods. Highlights: New chronologies constructed from two sediment cores in Baffin Bay (17–10 kyr BP). Two synchronous detrital carbonate (BBDC) events during deglacial. BBDC timing redefined as ∼14.2–13.7 kyr BP (BBDC 1) and ∼12.7–11 kyr BP (BBDC 0). BBDC events appear asynchronous with Laurentide Ice Sheet instabilities.